O14 Chemsex, consent and the rise in sexual assault. (8th June 2017) - Ward, Chris; McQuillan, Orla; Evans, Rebecca
Abstract : Introduction: Within the chemsex population reports of sexual assault, non-consensual sex and coercion are rising. We looked at consent among our chemsex clinic users. Methods: Retrospective data review of patients from April 2015 to March 2017. Data was collected on sexual assault, coercion, exploitation, risk taking, sexually transmitted infections and drug use. Results: 72 men were seen with a median age of 32. 41 (56.9%) were HIV positive, and 11 (15.3%) had Hepatitis C. 53 (73.6%) patients used Mephedrone, 40 (55.6%) GHB and 22 (30.6%) Crystal Meth. 13 (18.1%) patients reported self-harm. In total 23 (31.9%) patients reported non-consensual sex. A minority 5/30 (16.7%) were identified from April 2015 to Jan 2016 when using the terminology 'forced into sex'. After realising that addressing consent is more complex in this cohort, we prioritised consent discussions around unwanted sexual attention and from Jan 2016 to March 2017 18/42 (42.9%) reported non-consensual sex (Table 1). Discussion: Our data shows rates of non-consensual sex among chemsex users of up to 42.9%. There is a lack of patient understanding around what sexual assault and consent are and exploring this in a sensitive manner is paramount. Sexual assault discussions must be reviewed in both standard sexual health and chemsex clinics.